XPS investigation of titanium contact formation to ZnO nanowires - Richard Cobley (Nanotechnology, 2017)
Ti is often used to form an initial Ohmic interface between ZnO and Au due to its low work function, and the TiO2/ZnO heterojunction is also of great importance for many practical applications of nanoparticles. Here, Ti has been controllably deposited onto hydrothermally grown ZnO nanowires and the formation of metal–semiconductor contact has been investigated using x-ray photoelectron spectroscopy (XPS), photoluminescence (PL) spectroscopy and scanning electron microscopy. XPS results showed that that the Ti initially reacts with surface oxygen species to form TiO2, and further deposition results in the formation of oxides with oxidation state numbers lower than four, and eventually metallic Ti on top of the TiO2. The formation of TiC was also observed. XPS showed that the onset of metallic Ti coincided with a Zn 3p core level shift to lower binding energy, indicating upwards band bending and the formation of a rectifying contact. Annealing caused a near-complete conversion of the metallic Ti to TiO2 and caused the Zn 3p to shift back to its original higher binding energy, resulting in downwards band bending and a more Ohmic contact. PL measurements showed that the optical properties of the nanowires are not affected by the contact formation.